KUALITAS BAHAN KERING DAN BAHAN ORGANIK PAKAN KOMPLIT FERMENTASI BERBASIS DAUN GAMAL SECARA IN VITRO - Bachtaruddin Badewi; Bambang Hadisutanto (Politeknik Pertanian Negeri Kupang, 2020)
This study aims to determine the digestibility quality of dry matter and organic matter of complete fermented feed. This study used a completely randomized design with complete feed fermentation duration of 0 weeks, 3 weeks, 6 weeks and 9 weeks. The variables observed were the digestibility quality of dry matter and organic matter in vitro. The results showed that the dry matter digestibility of complete fermented feed at 0 weeks (48.508%) and 6 weeks (48.17%) was not significantly different (P> 0.05). Meanwhile, the complete dry matter digestibility of the fermentation time of 3 weeks (51.474%) and 9 weeks (44.558%) showed significant differences (P <0.05). Digestibility of complete feed organic matter with fermentation time of 0 weeks and 3 weeks did not show any difference but was significantly different from complete feed with 6 weeks and 9 weeks of storage. The conclusion of this study is the digestibility value of organic matter is higher than the value of dry matter digestibility because the digestibility of dry matter still contains ash and the digestibility of organic matter does not contain ash. Keyword : Complete Feed, Long Fermentation, In Vitro Digestibility